Evaluasi Fasilitas Sisi Darat Bandara Sultan Thaha Jambi Sebagai Bandar Udara Internasional - Lita Yarlina (WARTA ARDHIA, 2011)
Sultan Taha Syarifuddin Airport is an airport located in the province of Jambi. This airport began in April 2007 is managed by PT. Angkasa Pura II, which was previously managed by the Department of Transportation Jambi Province. PT.Angkasa Pura II (Persero) as the steering Airport, Jambi Sultan Taha Sultan Taha Airport development plan to be an international airport on 2012. Currently there are 5 air transport company which is every day in flight Sultan Taha Airport. Based on Forecast result (forecasting), the movement of aircraft on 2011 at 7.24%, 5.73% in 2012 and in 2013 5.429%. The number of passengers in 2011 rose 15.14% in 2012 rose 7.64% in 2013 rose 7.09%. While number of the cargo on 2011 rose 3%, 3% in 2012 and 2013, 3%. The analysis result of land side facilities at Sultan Taha Airport Jambi at departure are for the development of 274.31 m2 space. Need development of space for the arrivalare of 248 m2. Area of 134 m2 is adequate toilet but the toilet really badly because there are only 4 pieces of toilets currently available. Baggage claim area was not sufficient anymore the addition of 37.88 m2. Hall of arrival to the development of 311.51 m2. While fhe obstacles / problems related to building new terminal facilities of international standard can be implemented that is not related assets owned by DGCA is not handed over / transferred to PT.Angkasa Pura II (Persero) and there is still the official residence owned by DGCA.